Organizational Change and Performance of Public Parastatals: A Case of Uganda Registration Services Bureau Mbale Branch - Okiira Isaac (Uganda Christian University, 2024)
The purpose of this study was to investigate the relationship between Organizational change and performance at Uganda registration services Bureau. Utilizing a population of 45 and a sample size of 40 determined using the Solvene formula, the study applied a cross-sectional survey design. The research focused on three main objectives: assessing the impact of technological advancements, examining the role of leadership support, and evaluating the influence of risk management practices on performance. Regression analysis showed that technological advancements had a significant positive effect on performance (β = 0.65, p < 0.01), indicating that increased adoption of technology was associated with improved efficiency and productivity. Correlation results supported this finding, with a strong positive correlation (r = 0.72) between technological innovations and performance metrics. Leadership support also demonstrated a significant positive impact on performance (β = 0.58, p < 0.01), with a high correlation coefficient (r = 0.66) reflecting the importance of leadership in driving performance and fostering a supportive work environment. The study found that effective risk management practices positively influenced performance (β = 0.52, p < 0.05), supported by a moderate positive correlation (r = 0.57) between risk management and performance outcomes. The study concluded that technological advancements, strong leadership support, and robust risk management practices are critical to enhancing performance. It recommended that Uganda registration services Bureau invest in technology, enhance leadership training, and implement comprehensive risk management strategies to sustain and improve performance. The study’s implications emphasize the importance of strategic Organizational change for achieving long-term success and maintaining a competitive edge in the cooperative sector.